A genetic search based arrangement of load combinations in structural frames - Arslan, A; Turgut, P; Calayir, Y (Civil Comp Press, 1996)
[Abstract Not Available]
3rd International Conference in Computational Structures Technology -- AUG 21-23, 1996 -- BUDAPEST, HUNGARY